Ergonomics in the work environment of samu nurses: a view of nursing (Research, Society and Development, 2021)
Ergonomics is considered one of the main strategies in the prevention of some occupational diseases, and it is used with the objective of identifying unfavorable situations when carrying out activities in the work environment, in order to reduce risks without prejudice to professional performance. In this context, the Mobile Emergency Care Service constantly exposes its nursing workers to these circumstances, due to the specificities of direct patient care services outside the hospital environment, aiming at maintaining life in an urgent and emergency situation before arrival to a specialized service institution. The aim of this study was to evaluate scientific articles in the health field that address working conditions at SAMU and reflect on improvements in the nursing professional's work at SAMU. This is a bibliographic review carried out in the scientific databases Medline, Lilacs, Scielo and VHL. The following descriptors were used to select the articles: Physical ergonomics, Nursing, SAMU and Pre-hospital care. The results showed that nursing workers are exposed to numerous occupational risks caused by chemical, physical, mechanical, biological, ergonomic and psychosocial factors, it is important that they are informed and trained to avoid health problems, and control methods must be instituted to prevent accidents. In view of this, it is concluded that this study is relevant to the literature with regard to encouraging theoretical and practical knowledge about ergonomics in the hospital environment.